The Azambuja fault: An active structure located in an intraplate basin with significant seismicity (Lower Tagus Valley, Portugal) - Cabral, J. (2012)
The Azambuja fault is a NNE trending structure located 50 km NE of Lisbon, in an area of important historical seismicity. It is sited in the Lower Tagus Basin, a compressive foredeep basin related to tectonic inversion of the Mesozoic Lusitanian Basin in the Miocene. The fault is evident in commercial seismic reflection data, where it shows steep thrust geometry downthrowing the Cenozoic sediments to the east. It has also a clear morphological signature, presenting a NNE-SSW trending, east facing, 15 km long scarp, reaching a maximum height of 80 m. The fault scarp is the geomorphic appearance of a flexure expressed as a zone of distributed deformation, where Miocene and Pliocene sediments are tilted eastwards and are cut by steeply dipping meso-scale faults presenting reverse and normal offsets, with a net downthrow to the east. This pattern at the surface is compatible with a steep fault in the basement that tilts and branches through the overlying Cenozoic sedimentary cover. In order to constrain the neotectonic activity of this structure, detailed geological studies were conducted. Morphotectonics was studied through aerial photo interpretation, analysis of topographic maps and digital mapping. Those studies indicate Quaternary slip on the fault in the ranges of 0.05–0.06 mm per year. Seismogenic behaviour was assumed for the Azambuja fault based on the evidence of Quaternary tectonic activity and its location in an area of significant historical seismicity. Mw 6.4–6.7 maximum earthquakes, with recurrence intervals of 10000–25000 years, were estimated based upon the displaced morphological references, cumulative offsets and fault length.